Depressive Symptoms of the Main Character in Julie Anne Peters’ By the Time You Read This, I Will Be Dead - Rufi Lailatul Septia Ningrum; Robby Satria (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This research aims to determine the psychological problems, namely depression, of the main character in the